How countries link REDD+ interventions to drivers in their readiness plans: implications for monitoring systems - Salvini, Giulia; Herold, Martin; Sy, Veronique de; Kissinger, G.; Brockhaus, Maria; Skutsch, M. (IOP Publishing, 2014)
Countries participating in the REDD+ scheme are in the readiness phase, designing policy interventions to address drivers of deforestation and forest degradation (DD). In order for REDD+ interventions to be effective, it is essential that they take into account the specific drivers that they aim to address. Moreover it is crucial to design systems that monitor the effectiveness of the planned interventions. In this article we provide a comprehensive and comparative assessment of interventions proposed by 43 REDD+ countries in 98 readiness documents. We summarize the types of interventions and assess if they are formulated referring to the drivers of DD that they are aiming to address. Based on this assessment we consider the implications for systems for monitoring effectiveness of proposed interventions. Most countries reviewed link proposed interventions to specific drivers of DD. The majority of the countries making this link have better driver data quality, in particularly those that present their data in ratio or ordinal terms. Proposed interventions focus not only on activities to reduce deforestation, but also on other forest related REDD+ activities such as sustainable forest management, which reduce forest degradation and enhance forest stocks. Moreover, driver-specific interventions often relate to drivers not only inside but also outside the forest sector. Hence we suggest that monitoring systems need to assess not only deforestation rates through remote sensing, but also degradation and other carbon stock changes within the forest, using more detailed ground level surveys and measurements. In addition, the performance of interventions outside the forest need to be monitored, even if the impacts of these cannot be linked to specific changes in forest carbon stock in specific locations.